The Rigid Core and Flexible Surface of Amyloid Fibrils Probed by Magic‐Angle‐Spinning NMR Spectroscopy of Aromatic Residues. Issue 19 (27th March 2023) - Becker, Lea Marie; Berbon, Mélanie; Vallet, Alicia; Grelard, Axelle; Morvan, Estelle; Bardiaux, Benjamin; Lichtenecker, Roman; Ernst, Matthias; Loquet, Antoine; Schanda, Paul
Abstract: Aromatic side chains are important reporters of the plasticity of proteins, and often form important contacts in protein–protein interactions. We studied aromatic residues in the two structurally homologous cross‐β amyloid fibrils HET‐s, and HELLF by employing a specific isotope‐labeling approach and magic‐angle‐spinning NMR. The dynamic behavior of the aromatic residues Phe and Tyr indicates that the hydrophobic amyloid core is rigid, without any sign of "breathing motions" over hundreds of milliseconds at least. Aromatic residues exposed at the fibril surface have a rigid ring axis but undergo ring flips on a variety of time scales from nanoseconds to microseconds. Our approach provides direct insight into hydrophobic‐core motions, enabling a better evaluation of the conformational heterogeneity generated from an NMR structural ensemble of such amyloid cross‐β architecture. Abstract : Aromatic ring flips are a hallmark of "breathing motions" in proteins. But does the infinitely long β‐sheet structure of amyloids allow for such motions? In this study, we apply specific isotope labeling and solid‐state NMR to two amyloid fibrils to demonstrate that the motion of aromatic rings strongly differs between the core and the surface of the fibril.